Generation Z's prokem in social media: Language transformation and social identity of Makassar Adolescents - Musyarrafah S; Anang Santoso; Gatut Susanto (Universitas Muhammadiyah Malang, 2025)
The prokem utilized by Generation Z adolescents in Makassar represents a linguistic innovation influenced by the regional language of Makassar. This study seeks to identify and analyze the diverse forms of prokem employed by Generation Z adolescents in Makassar City, particularly on social media platforms. With the rapid advancement of information and communication technology, social media has emerged as a primary venue for adolescent social interaction, significantly impacting their language development. This research addresses the evolution of prokem, often perceived as an informal linguistic variation embodying elements of group identity, within a digital context, especially on platforms such as WhatsApp, Instagram and TikTok. The methodology employed in this research is discourse analysis, which utilizes a qualitative approach. Data were gathered through the observation and documentation of language posts or interactions by Generation Z adolescents in Makassar on social media. The analysis involved identifying the forms and patterns of prokem use and the social factors influencing its utilization and dissemination. The findings of this study reveal, first, that the forms of prokem used by Makassar adolescents include words, phrases, abbreviations, acronyms, interrogative words, and auxiliary words. Second, a comparison is drawn between the prokem of Makassar City adolescents and those from other regions. Third, the factors influencing the use of prokem among Generation Z adolescents on social media encompass interlocutors, conversation topics, kinship, social media platforms, emotional contexts, social groups, and prevailing trends. The prokem variety of Generation Z adolescents reflects a transformation in youth communication, characterized by openness to linguistic variations and adaptable social symbols. This research aims to contribute to the study of prokem in the contemporary context, particularly by exploring the interplay between language, social identity, and the evolution of communication technology among Indonesian adolescents. Bahasa prokem remaja generasi Z Kota Makassar merupakan inovasi berbahasa yang dipengaruhi oleh bahasa daerah Makassar. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis ragam bahasa prokem yang digunakan oleh remaja Generasi Z di Kota Makassar melalui media sosial. Seiiring dengan pesatnya perkembangan teknologi informasi dan komunikasi, media sosial menjadi salah satu ruang utama bagi interaksi sosial remaja, yang turut mempengaruhi perkembangan bahasa. Penelitian ini mengangkat persoalan tentang bagaimana bahasa prokem, yang seringkali dipandang sebagai bentuk variasi bahasa yang informal dan cenderung mengandung elemen identitas kelompok, berkembang dalam konteks digital, khususnya di platform media sosial seperti WhatsApp, Instagram, dan TikTok. Metode yang digunakan dalam penelitian ini adalah analisis wacana dengan pendekatan kualitatif. Data dikumpulkan melalui observasi dan dokumentasi terhadap unggahan atau interaksi bahasa yang dilakukan oleh remaja Generasi Z Kota Makassar di media sosial. Analisis dilakukan dengan mengidentifikasi bentuk, pola penggunaan bahasa prokem, dan faktor-faktor sosial yang mempengaruhi penggunaan dan penyebarannya. Hasil dari penelitian ini menunjukkan, pertama, bentuk bahasa prokem yang digunakan remaja Makassar berupa kata, frasa, singkatan, akronim, kata tanya, dan kata bantu. Kedua, ditemukan perbandingan antara bahasa prokem remaja Kota Makassar dengan remaja daerah lainnya. Ketiga, faktor yang memengaruhi penggunaan bahasa prokem remaja generasi Z di media sosial yang meliputi lawan bicara, topik pembicaraan, kekerabatan, platform media sosial, situasi emosional, kelompok sosial, dan tren. Ragam bahasa prokem remaja Generasi Z mencerminkan adanya pergeseran dalam cara berkomunikasi generasi muda yang lebih terbuka terhadap variasi bahasa dan simbol sosial yang bersifat fleksibel. Penelitian ini diharapkan dapat memberikan kontribusi terhadap kajian bahasa prokem dalam konteks kekinian, khususnya dalam menggali hubungan antara bahasa, identitas sosial, dan perkembangan teknologi komunikasi di kalangan remaja di Indonesia.